Assessing the level of serum heavy metals (lead, cadmium and arsenic) among Kota Bharu Firefighters - Ramlan, Shaqina (Universiti Sains Malaysia, 2016)
Firefighters are frequently exposed to significant concentrations of hazardous materials. They are exposed to smoke particles that spread through inhalation or skin and clothing contamination, with following absorption of adsorbed chemicals through the skin at the fire scene or at later times. This study aimed to investigate the occurrence of heavy metals (lead, cadmium and arsenic) in serum among firefighters. A crosssectional study design utilizing convenient sampling method was used to recruit 17 firefighters from Kota Bharu firestation as the exposed group and 17 staffs from Universiti Sains Malaysia, Health campus as the control group for this study. Blood samples were collected from all volunteer subjects and investigated for relevant parameters. Arsenic was the highest heavy metal level detected in Kota Bharu firefighters followed by lead and cadmium respectively. The results obtained showed that there was no significant difference in serum heavy metal levels in Kota Bharu firefighters as compared to normal control group (p>0.05). There was also no significant difference in serum heavy metals of Kota Bharu firefighters and normal control group and smoking status. It showed that lead and arsenic levels were higher among ex-smokers while cadmium levels were higher among smokers. Comparison between smoker and non-smoker group, smoker and ex-smoker group and nonsmoker and ex-smoker group showed no significant difference in all the groups tested. The varying recent fire incidents experienced by the firefighters may lead to the insignificant level of the heavy metals. Other factors may also influence the heavy metal levels such as smoking status, age, seafood intake, occupational factors and PPE usage. This study stresses on the importance of acknowledging the occupational exposure to fire smoke, personal hygiene and cleanliness as well as wearing personal protective equipment to minimize the risk of heavy metal exposure.